Methods of Control of the Manager Educational Institutions - Mahmudov Yusup Ganievich; Eshkarayev Aburahmat Hayitovich (Genius Publishing Group, 2022)
In this article, the author tells the essence of the management methods of the head of an educational institution.
Keywords: Management; result; process; achievement